Effectiveness of Quizizz in improving reading skills among dyslexic students - Subramaniam, Vijayaletchumy; Divagaran, Monisha; Kunasegran, Kavenia (Human Resources Management Academic Research Society (HRMARS), 2024)
Dyslexic students face challenges in the language domain. Language proficiency, that includes reading, writing and spelling among dyslexic students is generally very weak. According to Persatuan Dyslexia Malaysia (2023), dyslexic students have confusion in recognizing letters. Therefore, this research was conducted to study language mastery among dyslexic students through Quizzes. Quizizz is a platform for students to learn and answer questions according to the topics. Quizizz can be used as a short assessment in teaching and learning to find out the students’ knowledge and abilities. Teachers can create gamified Quizizz for students to grab the students’ attention. This research study sample consisted of 5 dyslexic students from the beginner grade level, who were selected from the TTDI Kuala Lumpur dyslexia center. The research instrument were 3 sets of reading tests that have been reviewed by dyslexia experts. The research data was then compiled through observation and testing. The researcher used test papers that were divided into 3 sets, such as letter recognition test, syllable test and reading test. Thus, the results of the study indicated that the language mastery among dyslexia students improved significantly through the application of Quizizz.